Treaty Crimes and Argentine Criminal Law: Internalization of Criminal Law and Its Effects on Domestic Law - Cordini, Nicolás Santiago (2022)
The establishment of criminal regulations of both substantive andprocedural law based on instruments of international law, known as theinternationalisation of criminal law, is not a new phenomenon. The novelty ofthis phenomenon is the scale at which it has spread. It is implemented throughvarious mechanisms, ranging from the cooperation between States,harmonization and approximation, to the integration of various criminal lawsystems. Harmonization presupposes a mechanism for the interaction of thevarious criminal law systems; in this sense, harmonization is an imperfectprocess, as the systems retain some of their differences. Internationalconventions delineate new criminal offences, commonly called "treaty crimes".In this paper, we propose to look at criminal harmonisation via the lens of treatycrimes. Our hypothesis is that the national legislator rarely deviates from thedefinition provided by the international standard, but does so on occasionswhere different obligations overlap or in cases of non-mandatorycriminalization. To that purpose, we will look at how several internationaltreaties have been applied in Argentine law, as well as how the obligations tocriminalize have been implemented.